Iron flame (Empyrean, 2, 1, 2024)
"Everyone expected Violet Sorrengail to die during her first year at Basgiath War College--Violet included. But Threshing was only the first impossible test meant to weed out the weak-willed, the unworthy, and the unlucky. Now the real training begins, and Violet's already wondering how she'll get through. It's not just that it's grueling and maliciously brutal, or even that it's designed to stretch the riders' capacity for pain beyond endurance. It's the new vice commandant, who's made it his personal mission to teach Violet exactly how powerless she is-unless she betrays the man she loves. Although Violet's body might be weaker and frailer than everyone else's, she still has her wits--and a will of iron. And leadership is forgetting the most important lesson Basgiath has taught her: Dragon riders make their own rules. But a determination to survive won't be enough this year. Because Violet knows the real secret hidden for centuries at Basgiath War College--and nothing, not even dragon fire, may be enough to save them in the end." --

Fourth wing (Empyrean, 1, 1, 2023)
"Twenty-year-old Violet Sorrengail was supposed to enter the Scribe Quadrant, living a quiet life among books and history. Now, the commanding general--also known as her tough-as-talons mother--has ordered Violet to join the hundreds of candidates striving to become the elite of Navarre: dragon riders. But when you're smaller than everyone else and your body is brittle, death is only a heartbeat away...because dragons don't bond to "fragile" humans. They incinerate them. With fewer dragons willing to bond than cadets, most would kill Violet to better their own chances of success. The rest would kill her just for being her mother's daughter--like Xaden Riorson, the most powerful and ruthless wingleader in the Riders Quadrant. She'll need every edge her wits can give her just to see the next sunrise. Yet, with every day that passes, the war outside grows more deadly, the kingdom's protective wards are failing, and the death toll continues to rise. Even worse, Violet begins to suspect leadership is hiding a terrible secret."--

Remarkably bright creatures: a novel (Harper Large Print, an imprint of HarperCollinsPublishers, Ecco, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, Harper Audio, 2022)
Staying busy has helped Tova cope ever since her son disappeared decades ago. So when her husband dies, she takes a job at the aquarium, where she meets Marcellus, an octopus that deduces what happened to her son. For fans of A Man Called Ove, a charming, witty and compulsively readable exploration of friendship, reckoning, and hope that traces a widow's unlikely connection with a giant Pacific octopus After Tova Sullivan's husband died, she began working the night shift at the Sowell Bay Aquarium, mopping floors and tidying up. Keeping busy has always helped her cope, which she's been doing since her eighteen-year-old son, Erik, mysteriously vanished on a boat in Puget Sound over thirty years ago. Tova becomes acquainted with curmudgeonly Marcellus, a giant Pacific octopus living at the aquarium. Marcellus knows more than anyone can imagine but wouldn't dream of lifting one of his eight arms for his human captors--until he forms a remarkable friendship with Tova. Ever the detective, Marcellus deduces what happened the night Tova's son disappeared. And now Marcellus must use every trick his old invertebrate body can muster to unearth the truth for her before it's too late. Shelby Van Pelt's debut novel is a gentle reminder that sometimes taking a hard look at the past can help uncover a future that once felt impossible.

Demon Copperhead: a novel (Harper Large Print, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, Harper, an imprint of HarperCollinsPublishers, Findaway World, LLC, Harper Audio, 2022)
Southern Appalachia. He was born to a teenaged single mother in a single-wide trailer, with no assets beyond his dead father's good looks and copper-colored hair, a caustic wit, and a fierce talent for survival. Damon braves the perils of foster care, child labor, derelict schools, athletic success, addiction, disastrous loves, and crushing losses. Through all of it, he reckons with his own invisibility in a popular culture where even the superheroes have abandoned rural people in favor of cities.

Tom Lake: a novel (Reese's book club, ,, 2023)
Recalling the past at her daughters' request, Lara tells the story of a famous actor with whom she shared both a stage and a romance, which causes her daughters to examine their own lives and reconsider the world and everything they thought they knew. "In the spring of 2020, Lara's three daughters return to the family's orchard in Northern Michigan. While picking cherries, they beg their mother to tell them the story of Peter Duke, a famous actor with whom she shared both a stage and a romance years before at a theater company called Tom Lake. As Lara recalls the past, her daughters examine their own lives and relationship with their mother, and are forced to reconsider the world and everything they thought they knew. Tom Lake is a meditation on youthful love, married love, and the lives parents have led before their children were born. Both hopeful and elegiac, it explores what it means to be happy even when the world is falling apart. As in all of her novels, Ann Patchett combines compelling narrative artistry with piercing insights into family dynamics. The result is a rich and luminous story, told with profound intelligence and emotional acuity, that demonstrates once again why she is one of the most acclaimed literary talents working today" --

The girl on the train (Books on Tape, Penguin Publishing Group, Penguin Audio, Thorndike Press, Riverhead Books, a member of Penguin Group (USA), 2015)
Rachel takes the same commuter train every morning. Every day she rattles down the track, flashes past a stretch of cozy suburban homes, and stops at the signal that allows her to daily watch the same couple breakfasting on their deck. She's even started to feel like she knows them. "Jess and Jason," she calls them. Their life -- as she sees it -- is perfect. Not unlike the life she recently lost. And then she sees something shocking. It's only a minute until the train moves on, but it's enough. Now everything's changed. Unable to keep it to herself, Rachel offers what she knows to the police, and becomes inextricably entwined in what happens next, as well as in the lives of everyone involved. Has she done more harm than good?

I'm glad my mom died (Simon & Schuster Audio, Simon & Schuster, 2022)
"Jennette McCurdy was six years old when she had her first acting audition. Her mother's dream was for her only daughter to become a star, and Jennette would do anything to make her mother happy. So she went along with what Mom called "calorie restriction," eating little and weighing herself five times a day. She endured extensive at-home makeovers while Mom chided, "Your eyelashes are invisible, okay? You think Dakota Fanning doesn't tint hers?" She was even showered by Mom until age sixteen while sharing her diaries, email, and all her income. In I'm Glad My Mom Died, Jennette recounts all this in unflinching detail--just as she chronicles what happens when the dream finally comes true. Cast in a new Nickelodeon series called iCarly, she is thrust into fame. Though Mom is ecstatic, emailing fan club moderators and getting on a first-name basis with the paparazzi ("Hi Gale!"), Jennette is riddled with anxiety, shame, and self-loathing, which manifest into eating disorders, addiction, and a series of unhealthy relationships. These issues only get worse when, soon after taking the lead in the iCarly spinoff Sam & Cat alongside Ariana Grande, her mother dies of cancer. Finally, after discovering therapy and quitting acting, Jennette embarks on recovery and decides for the first time in her life what she really wants." -- Amazon.com.

Lessons in chemistry: [a novel] (Knopf Doubleday Publishing Group, Penguin Random House, Random House Large Print, Books on Tape, Penguin Random House Audio, Doubleday, 2022)
"Set in 1960s California, this blockbuster debut is the hilarious, idiosyncratic and uplifting story of a female scientist whose career is constantly derailed by the idea that a woman's place is in the home, only to find herself starring as the host of America's most beloved TV cooking show. Elizabeth Zott is not your average woman. In fact Elizabeth Zott would be the first to point out that there is no such thing as an average woman. But it's the 1960s and despite the fact that she is a scientist, her peers are very unscientific when it comes to equality. The only good thing to happen to her on the road to professional fulfillment is a run-in with her super-star colleague Calvin Evans (well, she stole his beakers.) The only man who ever treated her-and her ideas-as equal, Calvin is already a legend and Nobel nominee. He's also awkward, kind and tenacious. Theirs is true chemistry. But as events are never as predictable as chemical reactions, three years later Elizabeth Zott is an unwed, single mother (did we mention it's the early 60s??) and the star of America's most beloved cooking show Supper at Six. Elizabeth's singular approach to cooking ('take one pint of H2O and add a pinch of sodium chloride') and independent example are proving revolutionary. Because Elizabeth isn't just teaching women how to cook, she's teaching them how to change the status quo. Laugh-out-loud funny, shrewdly observant, and studded with a dazzling cast of supporting characters, Lessons in Chemistry is as original and vibrant as its protagonist"--

The woman in me (Simon & Schuster Audio, Gallery Books, Thorndike Press Large Print, Simon & Schuster, 2024)
"In June 2021, the whole world was listening as Britney Spears spoke in open court. The impact of sharing her voice--her truth--was undeniable, and it changed the course of her life and the lives of countless others. The Woman in Me reveals for the first time her incredible journey--and the strength at the core of one of the greatest performers in pop music history. Written with remarkable candor and humor, Spears's groundbreaking book illuminates the enduring power of music and love--and the importance of a woman telling her own story, on her own terms, at last." --Amazon.

Killers of the Flower Moon: the Osage murders and the birth of the FBI (Random House Audio / Penguin Random House LLC, Knopf Doubleday Publishing Group, Penguin Random House, Random House Large Print, Findaway World, LLC, Vintage Books, A Division of Penguin Random House LLC, Books on Tape, Doubleday, 2018)
Presents a true account of the early twentieth-century murders of dozens of wealthy Osage and law-enforcement officials, citing the contributions and missteps of a fledgling FBI that eventually uncovered one of the most chilling conspiracies in American history. --Publisher
Chronicle one, the marked woman / read by Ann Marie Lee , Chronicle two, the evidence man / read by Will Patton , Chronicle three, the reporter / read by Danny Campbell.

The Fellowship of the Ring (Lord of the rings, 1, 1, 2007)
Begin your journey into Middle-earth... The inspiration for the upcoming original series on Prime Video, The Lord of the Rings: The Rings of Power. The Fellowship of the Ring is the first part of J.R.R. Tolkien's epic adventure The Lord of the Rings. One Ring to rule them all, One Ring to find them, One Ring to bring them all and in the darkness bind them. Sauron, the Dark Lord, has gathered to him all the Rings of Power—the means by which he intends to rule Middle-earth. All he lacks in his plans for dominion is the One Ring—the ring that rules them all—which has fallen into the hands of the hobbit, Bilbo Baggins. In a sleepy village in the Shire, young Frodo Baggins finds himself faced with an immense task, as his elderly cousin Bilbo entrusts the Ring to his care. Frodo must leave his home and make a perilous journey across Middle-earth to the Cracks of Doom, there to destroy the Ring and foil the Dark Lord in his evil purpose.

Oath and honor: a memoir and a warning (Hachette Audio, Little, Brown and Company, Hachette Book Group, 2023)
The House Republican leader who dared to take a stand against the January 6th insurrection, which she witnessed first-hand, and then helped lead the ensuing investigation, tells the story of this perilous moment in our history, the betrayal of the American people and the Constitution and the risks we still face.

The exchange: after The Firm (Firm, 2, 1, 2023)
"#1 New York Times bestselling author John Grisham delivers high-flying international suspense in a stunning new legal thriller that marks the return of Mitch McDeere, the brilliant hero of The Firm. What became of Mitch and Abby McDeere after they exposed the crimes of Memphis law firm Bendini, Lambert & Locke and fled the country? The answer is in The Exchange, the riveting sequel to The Firm, the blockbuster thriller that launched the career of America's favorite storyteller. It is now fifteen years later, and Mitch and Abby are living in Manhattan, where Mitch is a partner at the largest law firm in the world. When a mentor in Rome asks him for a favor that will take him far from home, Mitch finds himself at the center of a sinister plot that has worldwide implications--and once again endangers his colleagues, friends, and family. Mitch has become a master at staying one step ahead of his adversaries, but this time there's nowhere to hide"--

Educated: a memoir (Penguin Random House, Random House Large Print, Findaway World, LLC, Random House Publishing Group, Random House, Books on Tape, Random House Audio, 2018)
"Tara Westover was seventeen the first time she set foot in a classroom. Born to survivalists in the mountains of Idaho, she prepared for the end of the world by stockpiling home-canned peaches and sleeping with her "head-for-the-hills bag." In the summer she stewed herbs for her mother, a midwife and healer, and in the winter she salvaged in her father's junkyard. The family was so isolated from mainstream society that there was no one to ensure the children received an education, and no one to intervene when one of Tara's older brothers became violent. As a way out, Tara began to educate herself, learning enough mathematics and grammar to be admitted to Brigham Young University. Her quest for knowledge would transform her, taking her over oceans and across continents, to Harvard and to Cambridge. Only then would she wonder if she'd traveled too far, if there was still a way home. With the acute insight that distinguishes all great writers, Tara Westover has crafted a universal coming-of-age story that gets to the heart of what an education offers: the perspective to see one's life through new eyes, and the will to change it."--Provided by publisher.
Choose the good , The midwife , Cream shoes , Apache women , Honest dirt , Shield and buckler , The Lord will provide , Tiny harlots , Perfect in his generations , Shield of feathers , Instinct , Fish eyes , Silence in the churches , My feet no longer touch Earth , No more a child , Disloyal man, disobedient heaven , To keep it holy , Blood and feathers , In the beginning , Recitals of the fathers , Skullcap , What we whispered and what we screamed , I'm from Idaho , A knight, errant , The work of sulphur , Waiting for moving water , If I were a woman , Pygmalion , Graduation , The hand of the almighty , Tragedy then farce , A brawling woman in a wide house , Sorcery of physics , The substance of things , West of the sun , Four long arms, whirling , Gambling for redemption , Family , Watching the buffalo , Educated.

Dune (Dune novels. Main series, 1, 1, 2012)
Set on the desert planet Arrakis, Dune is the story of the boy Paul Atreides, who would become the mysterious man known as Maud'dib. He would avenge the traitorous plot against his noble family - and would bring to fruition humankind's most ancient and unattainable dream. A stunning blend of adventure and mysticism, environmentalism and politics, Dune won the first Nebula Award, shared the Hugo Award, and formed the basis of what is undoubtedly the grandest epic in science fiction.

The wind in the willows (BBC Children's Classics, ,, 2008)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.

The secret garden (Puffin classics, ,, 1998)
Ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden.

Treasure island (Everyman's library children's classics, ,, 2001)
Buried treasure. Villainous pirates. A brave boy in danger. Robert Louis Stevenson's thrilling tale of adventure on the high seas will delight young readers! With map in hand, Jim Hawkins sets sail to find Treasure Island, where a fortune is hidden. But evil buccaneer Long John Silver will stop at nothing to get that gold first ?
The old buccaneer , The sea cook , My shore adventure , The stockade , My sea adventure , Captain Silver.

Wild: from lost to found on the Pacific Crest trail (Knopf Doubleday Publishing Group, Alfred A. Knopf, Books on Tape, Thorndike Press, Random House Audio Publishing Group, 2013)
In the wake of her mother's death, Cheryl Strayed's family scattered and her marriage was destroyed. Four years later, twenty-six years old with nothing to lose, Cheryl made the decision to hike the Pacific Crest Trail from the Mojave Desert to Washington State - alone. She had no experience as a long-distance hiker and the trail was little more than an idea. But it was a promise of piecing back together a life that had come undone.

Resurrection walk (Mickey Haller novels, 7, 1, 2023)
Defense attorney Mickey Haller is back, taking the long shot cases, where the chances of winning are one in a million. He agrees to represent a woman in prison for killing her husband, a sheriff's deputy. Despite her conviction four years earlier, she still maintains her innocence. Haller enlists his half brother, retired LAPD Detective Harry Bosch, as investigator. Reviewing the case, Bosch sees something that doesn't add up, and a sheriff's department intent on bringing a quick search for justice in the killing of one of its own. The path to justice for both the lawyer and his investigator is fraught with danger from those who don't want the case reopened. And they will stop at nothing to keep the Haller-Bosch dream team from uncovering what the deputy's killing was really about.